Study on the classification of Descemet membrane detachment after cataract surgery with AS-OCT - Guo, Ping (Int J Med Sci, 2018)
In this article, the significance of anterior segment optical coherence tomography (AS-OCT) to aid the clinical diagnosis and treatment of Descemet membrane (DM) detachment after phacoemulsification combined with intraocular lens implantation was retrospectively analyzed using 26 patients (26 eyes). The location and scope of DM detachment, its causative factors and the percentage of each detachment type are considered for clinical treatments. Based on the location and scope, the detachment can be divided into three types: (1) simple, (2) symmetrical and (3) complete DM detachment. Simple detachment, confined to the area of surgical incision (detachment range <1/4 corneal area), occurred in 69.20 % of cases (18/26), in which the DM detachment in the anterior lip accounted for 42.30% (11/26) and in the posterior lip accounted for 26.90% (7/26). Symmetrical DM detachment, referring to detachment (1/4 cornea area < detached area <1/2 corneal area) that appeared symmetrically on the surgical incision and the opposite site, accounted for 19.20% (5/26). Complete DM detachment (>1/2 of the corneal area), accounted for 11.50% (3/26). Interestingly, our findings suggest that the DM detachment after phacoemulsification is closely related to the location (simple and symmetrical DM detachment) and the skillfulness (complete DM detachment) of the surgical incision. Therefore, appropriate classification of DM detachment by AS-OCT and wise selection of surgical location can better guide cataract surgery in the future.